PENCAHAYAAN, JARAK MONITOR, DAN PAPARAN MONITOR SEBAGAI FAKTOR KELUHAN SUBJEKTIF COMPUTER VISION SYNDROME (CVS) - Zulaiha, S; Rachman, Irwandi; Marisdayana, Rara (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2018)
Background: Computer Vision Syndrome (CVS) is a group of ocular problems (eyes and eyesight) complained by someone working on the computer for a long time. CVS be able to have an impact in daily activities, decreased work productivity, increased errors in work, and decreased job satisfaction. The aim of this study was to identify the factors related of CVS subjective complaints at PT Telkom Akses Jambi 2017. Method: This research was an analytic observational with cross-sectional design, the number of samples in this study using total sampling with inclusion criteria were all computer user workers amount of 41 workers. Data were analyzed by univariate and bivariate with fisher exact test. Results: The results of this study showed from 41 workers, there were 32 (78%) workers who have CVS complaints. The result of bivariate analysis by using fisher exact test showed there were significant between lighting intensity (p=0.020), monitor distance (p=0.006) and monitor exposure (p=0.000) with CVS subjective complaints and there were no significant between sex, age, years of work, length of working using computer, duration of eye rest a monitor posisition with CVS subjective complaints in computer workers in PT Telkom Akses Jambi. Conclusion: The intensity of lighting, the distance of the monitor, and the length of exposure of the monitor was significant with subjective complaints CVS in PT Telkom Akses Jambi. We suggest that the supervision of visual ergonomic computer be necessary in order to reduce the incidence of CVS in workers on a conditional basis, we also advise workers to take appropriate rest periods and stretches such as eye exercises when working.